Outer membrane and phospholipid composition of the target membrane affect the antimicrobial potential of first- and second-generation lipophosphonoxins - Látrová, Klára; Havlová, Noemi; Večeřová, Renata; Pinkas, Dominik; Bogdanová, Kateřina; Kolář, Milan; Fišer, Radovan; Konopásek, Ivo; Do Pham, Duy Dinh; Rejman, Dominik; Mikušová, Gabriela (Scientific reports, 2021)
Lipophosphonoxins (LPPOs) are small modular synthetic antibacterial compounds that target the cytoplasmic membrane. First-generation LPPOs (LPPO I) exhibit an antimicrobial activity against Gram-positive bacteria; however they do not exhibit any activity against Gram-negatives. Second-generation LPPOs (LPPO II) also exhibit broadened activity against Gram-negatives. We investigated the reasons behind this different susceptibility of bacteria to the two generations of LPPOs using model membranes and the living model bacteria Bacillus subtilis and Escherichia coli. We show that both generations of LPPOs form oligomeric conductive pores and permeabilize the bacterial membrane of sensitive cells. LPPO activity is not affected by the value of the target membrane potential, and thus they are also active against persister cells. The insensitivity of Gram-negative bacteria to LPPO I is probably caused by the barrier function of the outer membrane with LPS. LPPO I is almost incapable of overcoming the outer membrane in living cells, and the presence of LPS in liposomes substantially reduces their activity. Further, the antimicrobial activity of LPPO is also influenced by the phospholipid composition of the target membrane. A higher proportion of phospholipids with neutral charge such as phosphatidylethanolamine or phosphatidylcholine reduces the LPPO permeabilizing potential.
Keywords: Bacillus subtilis; Lipid Bilayers; vnější bakteriální membrána; Cell Membrane Permeability; membránové potenciály; lipidové dvojvrstvy; mikrobiální testy citlivosti; Escherichia coli; permeabilita buněčné membrány; kationické antimikrobiální peptidy; fosfatidylcholiny; Anti-Bacterial Agents; Phosphatidylcholines; Microbial Sensitivity Tests; fosfatidylethanolaminy; Bacterial Outer Membrane; Antimicrobial Cationic Peptides; Phosphatidylethanolamines; antibakteriální látky; Membrane Potentials